Loading web-font TeX/Math/Italic

y(y+6)=72

Simple and best practice solution for y(y+6)=72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y(y+6)=72 equation:



y(y+6)=72
We move all terms to the left:
y(y+6)-(72)=0
We multiply parentheses
y^2+6y-72=0
a = 1; b = 6; c = -72;
Δ = b2-4ac
Δ = 62-4·1·(-72)
Δ = 324
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
y_{1}=\frac{-b-\sqrt{\Delta}}{2a}
y_{2}=\frac{-b+\sqrt{\Delta}}{2a}

\sqrt{\Delta}=\sqrt{324}=18
y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-18}{2*1}=\frac{-24}{2} =-12
y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+18}{2*1}=\frac{12}{2} =6

See similar equations:

| 35=a/3+4 | | 8+7x-4x=13+2x | | 1/3(x+1)=1/2(x-2) | | 19+7y=5 | | 4+c15=-9 | | 8+(x-6)=-2=+2x-2 | | 7+2x=1-2x | | 2x=2235-5x | | 90+.6x=60+.90x | | 3x+76=144 | | 8-v=19 | | |x|=1.4 | | (12-3x)^3=0 | | A/10-3a/20=5/4-3a/10 | | 3(x+14)=27 | | 60/64=x/48 | | 1.6×n=6.4 | | 3x-7=11x-15 | | -2v+7=1+3v-6v | | X/12=1/3-x/12 | | 90=-18v | | -8v+6(v+7)=38 | | 9(x-1)-8=5x+4(-3+x) | | 9(x-1)-8=5x+4(-3+x | | -102-2x=-7 | | 2(3b+6)=-(8-4b) | | 4k=1.5k+50 | | 4x+5x+6=10 | | F(x)=15+2x^2 | | -39+3v=5(v-5) | | 5b-4-4=7b+8 | | −2(3z+1)−10=4−2(3z+1)−10=4 |

Equations solver categories